PENGARUH PEMBELAJARAN KONTEKSTUAL TERHADAP SIKAP PEDULI LINGKUNGAN PADA PEMBELAJARAN IPAS KELAS V DI SD NEGERI 196 PALEMBANG - Solahuddin; Hakim, Lukman; Mahendra, Agung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of contextual learning on the environmental care attitudes of fifth-grade students in Science and Social Studies (IPAS) learning at SD Negeri 196 Palembang. This research employed a quantitative approach using a Quasi-Experimental Design with the Nonequivalent Control Group Design. The population of this study consisted of all fifth-grade students at SD Negeri 196 Palembang in the 2026/2027 academic year, totaling 54 students. The sample was selected using an intact group technique, with Class VA serving as the experimental class and Class VB as the control class, each consisting of 27 students. Data were collected through observation, tests and documentation. The research instruments were tested for validity and reliability, and all items were declared valid with a Cronbach's Alpha coefficient of 0.868, indicating that the instrument was reliable and appropriate for use in the study. Data analysis included normality testing, homogeneity testing, and hypothesis testing using the Independent Samples t-test. The results indicated that contextual learning had a significant effect on students' environmental care attitudes in IPAS learning. This was evidenced by the significance value (Sig. 2-tailed) being less than 0.05, leading to the rejection of the null hypothesis (H₀) and the acceptance of the alternative hypothesis (Hₐ). Therefore, it can be concluded that contextual learning significantly improves students' environmental care attitudes by providing meaningful learning experiences, connecting learning materials with real-life situations, and encouraging students to actively participate in protecting and preserving the environment.